Różnorodne sposoby na weryfikację wiedzy – rozwiązania praktyczne - Kujawa-Weinke, Dorota (Tomorrow’s school? Tradition and (r)evolutions in education, 2023)
Assessment is an integral part of learning. If it is detached from the thoughtless insertion of the grade into the assessment journal that informs the student about what he knows and can do, it will also guide the teacher in planning and implementing the teaching process. This article presents strategies for obtaining information from students about their learning using a variety of applications and a variety of lesson monitoring techniques.